Extensive Variation in the Mutation Rate Between and Within Human Genes Associated with Mendelian Disease. Issue 5 (14th March 2016) - Smith, Thomas; Ho, Gladys; Christodoulou, John; Price, Elizabeth Ann; Onadim, Zerrin; Gauthier‐Villars, Marion; Dehainault, Catherine; Houdayer, Claude; Parfait, Beatrice; van Minkelen, Rick; Lohman, Dietmar; Eyre‐Walker, Adam
Abstract : We show that the rate of mutation varies substantially both with and between three genes associated with Mendelian disease: RB1, NF1 and MECP2. We find that the rate of CpG transition can be several hundred‐fold higher than the rate of non‐CpGtransversion mutation, much higher than the genomic average. We also find that the rate of all mutations, except CpG transitions, varies by at least 30‐fold within our three genes genes. ABSTRACT: We have investigated whether the mutation rate varies between genes and sites using de novo mutations (DNMs) from three genes associated with Mendelian diseases ( RB1, NF1, and MECP2 ). We show that the relative frequency of mutations at CpG dinucleotides relative to non‐CpG sites varies between genes and relative to the genomic average. In particular we show that the rate of transition mutation at CpG sites relative to the rate of non‐CpG transversion is substantially higher in our disease genes than amongst DNMs in general; the rate of CpG transition can be several hundred‐fold greater than the rate of non‐CpG transversion. We also show that the mutation rate varies significantly between sites of a particular mutational type, such as non‐CpG transversion, within a gene. We estimate that for all categories of sites, except CpG transitions, there is at least a 30‐fold difference in the mutation rate between the 10% of sites with the highest and lowest mutation rates. However, our best estimate is that the mutation rate varies by several hundred‐fold variation. We suggest that the presence of hypermutable sites may be one reason certain genes are associated with disease.